Analisis Kualitas Tidur dan VO₂max Tim Futsal Putra SMAN 1 Paciran Lamongan - Ananda Ryan Romadhon; Ananda Perwira Bakti (Journal of Creative Student Research, 2024)
SMAN 1 Paciran men's futsal team has failed in the last 2 years in participating in tournaments. Often the problem of decreased performance during matches is due to fatigue and some athletes are reluctant to maintain good sleep hours. The purpose of this study was to analyze sleep quality and VO₂max in male futsal athletes at SMAN 1 Paciran. This type of research uses quantitative analysis. The population is the men's futsal team of SMAN 1 Paciran with a sample of 15 athletes taken using a purposive sampling technique with the criteria of athletes aged 15-18 years. The data collected from the research results were then analyzed using the normality test, linearity test and hypothesis testing using the help of IBM Statistical Product and Service Solution (SPSS) 25 software. The results of the study show that both sleep quality and VO₂max variables have an important role in sports, especially futsal to display maximum performance during matches in participating in tournaments. If an athlete already has good VO₂max it is recommended to maintain good quality sleep, so that the athlete's VO₂max is maintained. Because good quality sleep can reduce the feeling of excessive fatigue during the game.